2023
DOI: 10.3389/fevo.2023.1114636
|View full text |Cite
|
Sign up to set email alerts
|

BMAA in cycad-feeding Lepidoptera: defensive sequestration or bioaccumulation?

Abstract: Many herbivorous Lepidoptera accumulate plant toxins within their own tissues as a defensive strategy. Pioneering research in this area was conducted by Miriam Rothschild and Deane Bowers, who showed that the cycad-feeding butterfly Eumaeus atala sequester the toxic plant compound cycasin and thereby deter vertebrate and invertebrate predators. The current study focuses on another cycad compound, β-methylamino-L-alanine (BMAA), that is known to accumulate in the tissues of insects and other herbivores, and whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Some cycad-feeding Aulacoscelinae beetles reflexively bleed MAM-glycosides -presumably sequestered from their foodplantswhen disturbed or threatened (Prado et al, 2011), and at least one lepidopteran has been shown to be capable of detoxifying MAM (Teas, 1967). Recently, the obligate cycad herbivore Eumaeus atalabutterfly was found to accumulate BMAA into their larval and adult tissues (Whitaker et al ., 2023), although the defensive value of sequestering BMAA remains questionable given its latent toxicity (Whitaker et al, 2022). Genomic evidence does suggest, however, that toxin tolerance is a key adaptation in the radiation ofEumaeus butterflies, a wholly cycadivorous neotropical genus of six species (Robbins et al, 2021).…”
Section: Parasitic Insect Herbivoresmentioning
confidence: 99%
“…Some cycad-feeding Aulacoscelinae beetles reflexively bleed MAM-glycosides -presumably sequestered from their foodplantswhen disturbed or threatened (Prado et al, 2011), and at least one lepidopteran has been shown to be capable of detoxifying MAM (Teas, 1967). Recently, the obligate cycad herbivore Eumaeus atalabutterfly was found to accumulate BMAA into their larval and adult tissues (Whitaker et al ., 2023), although the defensive value of sequestering BMAA remains questionable given its latent toxicity (Whitaker et al, 2022). Genomic evidence does suggest, however, that toxin tolerance is a key adaptation in the radiation ofEumaeus butterflies, a wholly cycadivorous neotropical genus of six species (Robbins et al, 2021).…”
Section: Parasitic Insect Herbivoresmentioning
confidence: 99%